Automated preparation of DNA sequences for publication. - Shapiro, M B (1986)
A computer program which draws DNA sequences is described. A simple method is used which enables the user to highlight or annotate specific parts of a sequence. The sizes of the characters in the sequence to be drawn are specified by the user. In addition, vertical spacing between lines and horizontal spacing between characters can be specified. Sequences can be prepared and high quality output produced on a plotter in a short period of time, making the program advantageous to use over typing, computer printing, or preparation by a graphics department.